Ramazzini Centret: the opening ceremony of the Danish Ramazzini Centre Århus, Denmark, April 2008 - Grandjean, Philippe (European Journal of Oncology and Environmental Health, 2008)
The occupational health research units in the western and northern part of Denmark have combined their resources and capabilities into a new collaborating research centre with the aim of developing and expanding the research into preventable causes of disease. The new centre is affiliated to the Aarhus University Hospital...